METHODOLOGY FOR THE EFFECTIVE ORGANIZATION OF MUSIC CLASSES IN PRESCHOOL EDUCATIONAL INSTITUTIONS - Djalilov , Ergash (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
Today, the effective organization of music classes in preschool educational institutions serves as a foundation for the development and proper guidance of children’s musical abilities. Therefore, developing an effective methodology for organizing music lessons is of great importance. This article analyzes issues related to planning music classes while considering children’s age and psychological characteristics, as well as the use of modern pedagogical technologies and interactive methods. In addition, the study reveals the role of music lessons in shaping children’s aesthetic taste, developing creative abilities, and enhancing their overall educational upbringing.